Era of The COVID-19 Pandemic: Ewuh Pakewuh Culture and Its Role on The Behavior of Someone in Debt, Based on Social Norms - Aprih Santoso; Rais Dera Pua Rawi; M. Hasan Ma'ruf (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to examine the effect of social norms on the behavior of a person in debt for small entrepreneurs in the city of Semarang in the era of the COVID-19 PANDEMI, with ewuh paewuh culture as a moderating variable. The population of this study includes all small entrepreneurs who take credit from the Wibawa in the city of Semarang, amounting to 3950 people. The number of samples is 100 people (based on the Slovin formula). The sample selection method is purposive sampling, with the following criteria: 1) small entrepreneurs taking debts for the first time. 2) Small entrepreneurs are married and still have dependents for school children. The results of this study indicate that social norms influence the behavior of a person in debt for small entrepreneurs in Semarang City during the COVID-19 PANDEMIC era and the ewuh pakewuh culture is able to moderate the relationship between the influence of social norms on this behavior.